Do Women Have More Shame than Men? An Experiment on Self-Assessment and the Shame of Overestimating Oneself - Sandra Ludwig; Carmen Thoma (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2012)
We analyze how subjects' self-assessment depends on whether its accuracy is observable to others. We find that women downgrade their selfassessment given observability while men do not. Women avoid the shame they may have if others observe that they overestimated themselves. Men, however, do not seem to be similarly shame-averse. This gender difference may be due to different societal expectations: While we find that men are expected to be overconfident, women are not. Shame-aversion may explain recent findings that women shy away from competition, demanding jobs and wage negotiations, as entering these situations is a statement to be confident of one's ability.
urn:nbn:de:bvb:19-epub-12905-6
Keywords: C91; D03; J16; 330; Gender; Shame; Self-confidence; Overconfidence; Experiment; Selbstevaluation; Persönlichkeitspsychologie; Geschlecht; Test